O tema da loucura na literatura, na pintura e no cinema: três diferentes perspetivas - Fernanda Monteiro Vicente (Carnets)
Literature, painting and cinema convey different perceptions of the extravagant experience of madness. This article analyses some examples of each of these manifestations, such as excerpts from the narrative work of Júlio Dinis, a 19th century Portuguese writer, paintings by Robert-Fleury Tony and Gericault, dating from the same period, and finally the film A Beautiful Mind (2001), offering a Foucaultian view on this matter. The works of Michel Foucault, The hermeneutics of the subject (2006) and History of madness (2005), allow addressing “the self-care” in a power-knowledge-freedom relationship axis as well as the importance that the awareness of the self, of others and of the world has in the process of creating their ethical existence, regarding the never completed transformation of the subject. The aim is also to ascertain to what extent each of these art forms reveals Foucault's theoretical assumptions.